2017
DOI: 10.5301/tj.5000621
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of GSTM1 and GSTT1 Genes and Lung Cancer Survival: a Systematic Review

Abstract: Purpose The mechanisms of lung carcinogenesis are not fully understood. Not all smokers develop lung cancer, indicating that genetic variations and other environmental factors may play an important role in its development. The human glutathione S-transferases (GSTs) have been associated with an increased risk of lung cancer. Glutathione S-transferases are phase II biotransformation enzymes that play a role in detoxifying a wide range of exogenous agents including carcinogens but also anticarcinogenic drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…According to reports in the literature, the American GSTM1 gene deletion rate is 23-62%, Europeans 39-62%, Africans 23-48%, and Asians 33-63%. 39 The GSTT1 gene deletion rate is roughly 22-31% for Americans, 10-21% for Europeans, 15-26% for Africans, and 16-64% for Asians. 39 The GSTM1 and GSTT1 gene deletion rates are extensively regional and racially diverse, which may be due to differences in exposure to geographic differences, environment, and diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to reports in the literature, the American GSTM1 gene deletion rate is 23-62%, Europeans 39-62%, Africans 23-48%, and Asians 33-63%. 39 The GSTT1 gene deletion rate is roughly 22-31% for Americans, 10-21% for Europeans, 15-26% for Africans, and 16-64% for Asians. 39 The GSTM1 and GSTT1 gene deletion rates are extensively regional and racially diverse, which may be due to differences in exposure to geographic differences, environment, and diet.…”
Section: Discussionmentioning
confidence: 99%
“…39 The GSTT1 gene deletion rate is roughly 22-31% for Americans, 10-21% for Europeans, 15-26% for Africans, and 16-64% for Asians. 39 The GSTM1 and GSTT1 gene deletion rates are extensively regional and racially diverse, which may be due to differences in exposure to geographic differences, environment, and diet. Our results show that the gene deletion rate of GSTM1 is 36.4%, consistent with the above results.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Ren et al observed that the presence of ERCC1 rs11615 polymorphism (C/T or T/T) was associated with longer survival (p = 0.014) 30 . Furthermore, Ramos et al in a recent systematic review, analyzed the association between GSTM1 and GSTT1 deletion and survival, concluding that most studies showed no effect or a slight trend towards a worse survival 13 . As can be seen, the results reported by these papers cited are heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…This could be one reason why no association with survival is observed in never-smokers. GSTM1 and/or GSTT1 deletion produces an absence of enzymatic activity with an enhanced effect of chemotherapy treatment, greater oxidative damage in tumor cells and ensuingly higher toxicity, causing an expected probable increase in survival 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, individuals homozygous for the GSTM1 or GSTT1-null allele have a complete absence of GSTM1 and GSTT1 activity, whereas individuals with two copies of the GSTM1 or GSTT1 genes have reference protein levels. 12,13 There is some evidence that these deletion genotypes may play a role in toxicity, response to treatment, and survival in some cancers, [14][15][16] including cancer of the ovary. 8 In contrast to the commonly studied GSTM1 and GSTT1 genotypes, the GSTP1 c.313A>G (rs1695) is an exonic single nucleotide polymorphism (SNP) that causes an amino acid substitution and results in an isoleucine to valine (Ile > Val) change at codon 105 of the enzyme.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%